Collaborative governance in the blue economy and green finance: taking the Eastern blue economic circle of China as a sample - Zhang, Xiao; Dai, Yuhui; Cao , Songwei (Transformations In Business & Economics, 2026)
In the context of accelerating global climate change, environmental challenges, and growing resource constraints, green finance and its synergistic development with the blue economy have attracted significant attention as crucial mechanisms for promoting sustainable economic growth. However, existing studies have predominantly focused on unidirectional influences between the blue economy and green finance, with limited attention to their potential bidirectional interplay. To explore the relationship between the blue economy and green finance, employing cointegration theory and the Entropy Weight-TOPSIS model, the comprehensive development levels of the blue economy and green finance were measured in China’s eastern blue economic circle from 2002 to 2024. Granger causality tests were further applied to examine the coupling coordination degree between the two systems and to verify the presence of a long-term equilibrium and causal relationship during the study period. Results show that a significant coupling relationship between green finance and the blue economy, alongside a stable long-term cointegration relationship. In the short run, however, the two systems exhibit a negative correlation. Moreover, green finance is identified as a Granger cause of the blue economy, underscoring its substantial influence. These conclusions serve to enrich the literature on the coordinated development of green finance and the blue economy, and can be referenced to develop policy recommendations for urban policymakers.
Keywords: blue economy; green finance; coupled coordination analysis; co-governance